Passive immunotherapy using approved vaccines combined with lockdown, as essential parts of the community medicine and public health to survive and even beat COVID: A viewpoint commentary - Jerard Seghatchian (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Mass vaccination campaigns are still underway to help in combatting the COVID-19 pandemic but timely production and distribution of approved vaccines is becoming a major unresolved problem worldwide. Meanwhile some new generation of vaccines, developed based on the characteristic profiles of the viral spike proteins and when deployed in the planned mass vaccination studies in the UK were found to be highly effective, to slow down the rate of hospitalization and to save life, Where the use of artificial intelligence and newer technological tools in big data and patterns analysis, were instrumental that we could not do without.